(untitled) (Diametros, 2010)
In England and Wales, there is significant controversy on the law related to abortion. Recent discussions have focussed predominantly on the health professional’s right to conscientious objection. This article argues for a comprehensive overhaul of the law from the perspective of an author who adopts the view that all unborn human beings should be granted the prima facie right to life. It is argued that, should the law be modified in accordance with this stance, it need not imply that health professionals should enjoy an unqualified right to object to participating in the provision of abortion. Indeed, it is proposed that – in some situations – women should be granted a positive right to abortion. While the focus of this article is on changing the law in England and Wales, it is hoped that the position developed here will also inspire legal debate and reform elsewhere.